Internet of Things and Smart Technologies in Oral Health: Trends, Impacts, and Challenges - Susana J. Calderon; Stephen Mujeye Sr; Melissa I. Calvillo (Oral)
Objective: This study aims to discover the most current trends, impacts, and challenges of using IoT devices and smart technologies in oral health. Method: A modified systematic mapping method was used to generate and answer five research questions. Twelve databases were queried to identify published literature from 2017 to 2023. Abstract screening and full-text review were conducted to identify studies meeting inclusion criteria. The Pandas library in Python Version 3.9.19 and a Fibonacci series were used to identify keyword trends in abstracts. Full-text analysis was conducted to synthesize findings relevant to the impacts and challenges of IoDT. Results: A total of 958 unduplicated articles were identified from the literature databases. After review, 33 articles were included. Publications related to IoDT are rapidly increasing over the last 7 years and keywords relating to toothbrushing were the most common. The most common research strategy was design and creation, followed by experimental methods. Design and creation of smart technologies in oral health are in a phase of measurement optimization using IoT which is being used for prevention, early detection, monitoring, and treatment of dental disease as well as silent communication devices. Challenges in IoDT continue to include measurement accuracy and user acceptability. Conclusions: Research in IoDT is predicted to continue to advance rapidly. Dental providers and public health agencies can look to this research to develop best practices. However, more research on how IoDT can facilitate desirable outcomes in a cost-effective and user-friendly way is needed.